The lexical minimum as the basis of teaching the Russian vocabulary to foreign students - Копилова, О.; Курилюк, Т. (Teaching Languages at Higher Educational Establishments at the Present Stage. Intersubject Relations, 2017)
The article deals with the concept of the «lexical minimum» and approaches to creating a lexical minimum in the European and Russian linguodidactics. The authors analyze the function of the lexical minimum in lexical component modeling of foreign student’s communicative competence. They give the main characteristics of a lexical minimum and present classification of such dictionaries in accordance with research works on lexicography. It is noted that different approaches to a dictionary entry structure and the dictionary itself, in the methods of selecting the vocabulary and the criteria for selecting words are observed in all subtypes of the lexical minimum dictionaries. The problem of selecting a vocabulary for a particular foreign language level, in a way, remains unsolved. This occurs because of many reasons including the fact that the cognitive, functional and didactic value of different words is not always the same as language is an ever-changing system. The main aim of the process of minimizing lexical content of a non-native language (second language) is to create a lexical basis of foreign language communicative skills in the most appropriate way. The function of the lexical minimum in linguodidactics is to regulate the process of vocabulary formation and to determine the lexical component of the foreign student teaching process. The minimization basis is the process of object reducing while its principal properties remain the same. In this regard, the language vocabulary is one of the most difficult objects of minimization. Formation of a lexical minimum must meet the teaching process requirements. The authors consider the concepts of “lexical minimum of general knowledge” (lexical minimum of the Language for General Purposes) and “lexical minimum of professional communication” (lexical minimum of the Language for Specific Purposes). From the methodological point of view, the minimum of professional communication occupies the second position after the minimum of general knowledge so the primary task is to create the lexical minimum dictionaries of the Language for General Purposes. The article contains an analysis of the main criteria for selecting lexical unit relevant for a modern lexical minimum, in particular for the standardized and normatively fixed graduation series of lexical minimums of the TORFL. There have been proposed principles of vocabulary selection not mentioned before but implicitly considered in the lexical minimum dictionary formation. The article also includes recommendations for compiling a general knowledge lexical minimum and its further application for teaching foreign students.